2013
DOI: 10.3109/13693786.2012.698444
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofParacoccidioidesspp. in environmental aerosol samples

Abstract: Taking into account that paracoccidioidomycosis infection occurs by inhalation of the asexual conidia produced by Paracoccidioides spp. in its saprobic phase, this work presents the collection of aerosol samples as an option for environmental detection of this pathogen, by positioning a cyclonic air sampler at the entrance of armadillo burrows. Methods included direct culture, extinction technique culture and Nested PCR of the rRNA coding sequence, comprising the ITS1-5.8S-ITS2 region. In addition, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 34 publications
6
41
0
3
Order By: Relevance
“…Another study, detecting P. lutzii DNA in aerosols from the southeast region of Brazil, had already suggested that this fungus could not exist exclusively in the Midwest region of the country as previously proposed . Our results corroborate with this study, suggesting the presence of P. lutzii also in southern Brazil.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study, detecting P. lutzii DNA in aerosols from the southeast region of Brazil, had already suggested that this fungus could not exist exclusively in the Midwest region of the country as previously proposed . Our results corroborate with this study, suggesting the presence of P. lutzii also in southern Brazil.…”
Section: Discussionsupporting
confidence: 92%
“…7 Phylogenetic studies about the aetiological agent of the disease found that Paracoccidioides brasiliensis corresponds to a complex of species: P. brasiliensis (S1, PS2, PS3, PS4) and P. lutzii, with descriptive occurrence in geographical areas of Brazil, Argentina, Peru, Paraguay, Venezuela (S1 and PS2) and Colombia (PS3). 8,9 The subspecies PS4 was most recently isolated in Venezuela 10,11 and P. lutzii was recently described in Brazil. 8 Few data are described in the literature concerning the infection by this new PCM agent, P. lutzii.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Arantes and others 27 reported environmental nucleic acid sequences belonging to P. lutzii in the hyperendemic region of Botucatu in the southeast region of Brazil, 27 an area formerly assumed to have a high prevalence of species S1. [2][3][4] However, no increase in clinical cases of PCM caused by P. lutzii has been seen in areas others than the central-west region of Brazil, which could be related to differences in the survival and growth of this species in nature, differences in human exposure, or even host resistance to infection in this area, and the misidentification of this pathogenic species by currently available techniques.…”
mentioning
confidence: 99%
“…Such results suggest that there are differences in the fungus antigenic composition of P. brasiliensis . Arantes et al [27] collected aerosol samples for the environmental detection of Paracoccidioides ssp. , by placing a cyclonic air sampler at the entrance of the armadillo burrow in Botucatu (SP).…”
Section: Discussionmentioning
confidence: 99%